Images of Ticks Submitted to the Swedish Veterinary Agency During 2023 - Department of Chemistry, Environment and Feed Hygiene, Swedish Veterinary Agency (Swedish Veterinary Agency, 2026)
This dataset contains all verified reports of tick sightings with corresponding images reported by the public to the "Rapportera Fästing" platform (https://rapporterafasting.sva.se/) during 2023 (starting in May when the platform was launched). The platform is developed and maintained by the Swedish Veterinary Agency (SVA) within the scope of the European project IDAlert (https://idalertproject.eu/). The dataset is provided by SVA and is licensed under CC BY 4.0 (https://creativecommons.org/licenses/by/4.0/).

The dataset includes two files: ticks_2023.zip, which contains the tick image files, and ticks_2023.csv, which contains metadata about each report. The dataset contains 12,154 reports with corresponding images.

Denna dataset innehåller alla verifierade rapporter om fästingobservationer med tillhörande bilder som allmänheten har rapporterat till plattformen ”Rapportera Fästing” (https://rapporterafasting.sva.se/) under 2023 (från och med maj då plattformen lanserades). Plattformen utvecklas och underhålls av Statens veterinärmedicinska anstalt (SVA) inom ramen för det europeiska projektet IDAlert (https://idalertproject.eu/). Datasetet tillhandahålls av SVA och är licensierat under CC BY 4.0 (https://creativecommons.org/licenses/by/4.0/).

Datasetet innehåller två filer: ticks_2023.zip, som innehåller bildfilerna på fästingar, och ticks_2023.csv, som innehåller metadata om varje rapport. Datasetet innehåller 12 154 rapporter med tillhörande bilder.
Fästingbilder som skickats in till Statens veterinärmedicinska anstalt under 2023
Keywords: Ticks; Fästingar; Artificial Intelligence; Artificiell intelligens; image classification; bildklassifiering; image analysis; citizen science; medborgarforskning; Ixodida; fästingar; Climate Science; Klimatvetenskap; Epidemiology; Epidemiologi; Other Veterinary Science; Annan veterinärmedicin